Strategy for the Development of Istana Amal Beach Tourism Objects in North Penajam Paser Regency - Mei Vita Romadon Ningrum; Haris Setiawan (Universitas Lambung Mangkurat, 2023)
Penajam Paser Utara Regency is one area with much marine tourism, one of which is beach tourism. Istana Amal Beach Tourism Object is a tourist attraction with a beautiful natural charm and complete and adequate facilities, so many local and foreign tourists come to enjoy the natural beauty and the facilities. This research aims to identify the development strategy of the Istana Amal Beach tourist attraction in North Penajam Paser Regency. This type of research uses descriptive qualitative research. Data collection techniques using purposive sampling were obtained from observations, interviews, questionnaires, and documentation conducted with 100 informants of tourist attraction managers, local traders, and tourists. SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) is used to determine development strategies. The results showed that the strategy that can be carried out in the development of Istana Amal Beach tourism is the SO (Strengths & Opportunities) strategy, namely by utilizing the potential of the beach, which has a location strategy by adding facilities to provide comfort and safety for visitors, as well as increasing offline media promotions to promote Istana Amal Beach attractions more widely.